Surrounded by liars : how to stop half-truths, deception, and gaslighting from ruining your life - Erikson, Thomas, 1965- (St. Martin's Essentials, 2024)
"Protect yourself against lies and deception with bestselling author Thomas Erikson's proven behavioral science methods Do you ever have the feeling that your friend isn't telling you the whole story? Or that your colleague's answer doesn't quite add up? Whether in your personal or social life, professional life, or on the news or media, sorting the lies from the truth can be exhausting and make you feel constantly on edge. In the next installment of the Surrounded by Idiots series, Thomas Erikson shows you how to identify and deal with the liars in your life. With the help of the simple, four-color behavioral model made famous in Surrounded by Idiots, readers will learn to protect themselves against deception and insincerity. Filled with sophisticated wisdom and Erikson's trademark humor, SURROUNDED BY LIARS arms readers with the practical knowledge needed to feel confident in their ability to discern the truth and live a calmer, more reliable life"--